World Protests - Ortiz, Isabel. author. aut Link
XIX, 185 p. 38 illus. in color.
Keywords: This is an open access book. The start of the 21st century has seen the world shaken by protests, from the Arab Spring to the Yellow Vests, from the Occupy movement to the social uprisings in Latin America. There are periods in history when large numbers of people have rebelled against the way things are, demanding change, such as in 1848, 1917, and 1968. Today we are living in another time of outrage and discontent, a time that has already produced some of the largest protests in world history. This book analyzes almost three thousand protests that occurred between 2006 and 2020 in 101 countries covering over 93 per cent of the world population. The study focuses on the major demands driving world protests, such as those for real democracy, jobs, public services, social protection, civil rights, global justice, and those against austerity and corruption. It also analyzes who was demonstrating in each protest; what protest methods they used; who the protestors opposed; what was achieved; whether protests were repressed; and trends such as inequality and the rise of women’s and radical right protests. The book concludes that the demands of protestors in most of the protests surveyed are in full accordance with human rights and internationally agreed-upon UN development goals. The book calls for policy-makers to listen and act on these demands. Isabel Ortiz is Director of the Global Social Justice Program at the Initiative for Policy Dialogue at Columbia University, USA, and former Director at the United Nations’ International Labor Organization and UNICEF. Sara Burke is Senior Policy Analyst at the Friedrich-Ebert-Stiftung New York, USA. Mohamed Berrada is a Senior Economist and Independent Consultant. Hernán Saenz Cortés is Senior Researcher on Inequality and Tax and Advocacy Coordinator on European Union - Latin America relations at OXFAM.